Challenges and Opportunities for the Implementation of the Concept of Missionary Ralph Winter (E1) in the Church Mission at the GKI Port Numbay Jayapura Classis - Mofu, Benyamin Dadi Ratu; Kolibu, Dirk (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This paper aims to analyze the challenges of implementing the E1 concept and identify opportunities in the mission of the church in the GKI Port Numbay Jayapura Classis. The literature review approach is the method used in this study, because it provides the theoretical foundation and context needed to understand the application of the concept of Ralph Winter (E1) missionaries in the church mission in the GKI Port Numbay Classis. The literature review also includes an analysis of the challenges faced in the application of the E1 concept. The E1 concept, emphasizing mission in a cultural context, demonstrates the urgent need to understand and appreciate local cultures. This requires the church to innovate in the way the gospel message is delivered to be relevant to the local context. There is a great opportunity to build close relationships with local communities. Programs that involve the active participation of congregations showing increased attendance and their involvement in services are expected to serve as agents of change that not only spread the gospel but also empower local communities (congregations). It is hoped that the church will continue to innovate in mission methods that are in accordance with the cultural and social context of the community, so that it can reach more individuals and communities